Abnormal haemostasis in small cell lung cancer. Issue 12 (December 1988) - Milroy, R; Douglas, J T; Campbell, J; Carter, R; Lowe, G D; Banham, S W
Abstract : Disorders of haemostasis and altered platelet activity have been documented in patients with malignant disease but their relation to response to treatment and prognosis are not known. Thrombin activity (fibrinopeptide A (FpA), plasmin mediated fibrinolysis (B beta 15-42) antigen), and platelet alpha granule release (beta thromboglobulin) were studied in 37 patients with small cell lung cancer to find out whether these indices show a relationship to chemoresponse. There was evidence of considerably increased thrombin activity, with a median fibrinopeptide A concentration of 13.2 (normal less than 4) pmol/ml, but only modestly increased fibrinolysis, with a median B beta 14-42 antigen concentration of 5.6 (normal less than 3) pmol/ml. Thus the ratio of fibrinopeptide A to B beta 15-42 concentration (FpA:B beta) was raised, with a median value of 2.2 (normal less than 1.33). In addition, 57% of patients had increased platelet alpha granule release, the median beta thromboglobulin concentration being 50 (normal less than 50) ng/ml. There was a significant association between increased thrombin generation and lack of response to chemotherapy. Furthermore, non-responders had higher FpA:B beta ratios. The same haemostatic markers were studied in nine patients who have been in complete remission for at least two years after chemotherapy for small cell lung cancer. There was a significant difference in thrombin activity and also in the ratio of thrombin activity to lysis between the pretreatment group and the group of two year survivors. Lack of response to chemotherapy appears to be related to increased thrombin activity. Such an association has not previously been reported in patients with malignant disease.